The important accounting graduates skills for the Libyan job market: perceptions of academics and professionals (Journal of Management and Business Education, 2023)
The purpose of this study is twofold. First, it aims to explore the important accounting graduate skills namely accounting technical skills, computer accounting skills, and general skills for the Libyan job market. Second, it aimed to investigate whether the opinions of academics and professionals are different regarding accounting technical skills, computer accounting skills, and general skills. The study used 100 questionnaires received from academics and professionals and used descriptive statistics, one sample t-test and independent samples t-test to test the hypothesis of the study. The findings showed that the selected accounting graduates’ skills particularly accounting technical skills, computer accounting skills, and general skills are important for the Libyan job market. Also, the results revealed no differences between the perceptions of academics and professionals regarding the important accounting graduate skills in the Libya job market.
Keywords: Libyan Job; market needs; technical skills; computer accounting skills; general skills; accounting graduates